1978
DOI: 10.1161/01.cir.58.5.803
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sublingual nitroglycerin on regional flow in patients with and without coronary disease.

Abstract: SUMMARY We evaluated the effects of sublingual nitroglycerin on indices of regional coronary flow and coronary resistance (CR) in 12 selected patients with coronary artery disease (CAD) and eight with normal coronary arteries (NCA), using continuous thermodilution. Resting total left ventricular flow, reflected by coronary sinus flow (CSF), and anterior regional flow, reflected by great cardiac vein flow (GCVF), in NCA and CAD patient groups, were similar. However, in a subgroup of six patients, with CAD limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…6,15,16 The functional impairment of a vessel is probably better assessed by measuring flow reserve. Invasive studies have shown that when maximal coronary dilatation is induced, blood flow or blood flow velocity increases more in normal vessels than in those affected by significant stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…6,15,16 The functional impairment of a vessel is probably better assessed by measuring flow reserve. Invasive studies have shown that when maximal coronary dilatation is induced, blood flow or blood flow velocity increases more in normal vessels than in those affected by significant stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In addition, all of these drugs are thought to induce a redistribution of coronary blood flow between normal and ischemic myocardium, and some may also have direct protective effects on the myocardium." [15][16][17][18][19][20][21] Because the ischemia in patients with coronary artery disease is regional, major interest has been directed to the study of regional differences in myocardial perfusion and function. Investigations in conscious experimental animals with chronic coronary arterial stenosis indicated that exercise causes severe regional myocardial dysfunction and hemodynamic abnormalities.…”
mentioning
confidence: 99%
“…' " By reducing intraventricular diastolic pressure, it improves the transmural distribution of myocardial perfusion by reducing extrinsic diastolic compression of the subendocardial vessels. 6 No 6, DECEMBER 1981 rest pain with associated ST-segment depression. Premedication was usually avoided; all cardiac medications were discontinued at least 10 hours before the procedure.…”
mentioning
confidence: 99%